A comparative study of fruit and vegetable consumption and physical activity among adolescents in 49 Low-and-Middle-Income Countries - Sandra A. Darfour-Oduro (Nature Portfolio, 2018)
Abstract Physical inactivity and low consumption of fruits and vegetables (FV) during adolescence may persist through adulthood, putting adolescents at risk of developing chronic diseases. Although studies from high-income countries have reported differences in FV consumption and physical activity (PA) between adolescent boys and girls, few exist from low-and-middle-income countries (LMICs). In this study, we examined patterns of FV consumption and PA among adolescent boys and girls in LMICs. Country selection was based on availability of Global School-Based Student Health Survey (GSHS) data from 2004 to 2013. The total analytic sample was 164,771 adolescents from 49 LMICs. Descriptive statistics were generated to determine adolescents meeting the World Health Organization (WHO) recommendations for FV and PA. A Rao-Scott adjusted chi-square statistic was computed to assess gender differences. Less than 30% of adolescents across all countries met the WHO guidelines for FV consumption or PA. Morocco (29.5%) and India (29.5%) however had the highest percentage of adolescents meeting recommendations for FV and PA, respectively. Adolescent boys were more active than girls, and this difference was more notable in the Middle East and North African region. Adolescents achieving the WHO recommendations for daily consumption of FV and PA were consistently low in all countries.